If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 = 12 + -68 Reorder the terms: -5 + 5x = 12 + -68 Combine like terms: 12 + -68 = -56 -5 + 5x = -56 Solving -5 + 5x = -56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5x = -56 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = -56 + 5 5x = -56 + 5 Combine like terms: -56 + 5 = -51 5x = -51 Divide each side by '5'. x = -10.2 Simplifying x = -10.2
| f(x)=2x(4)-3x+4 | | 4x+13=8x+25 | | -x+42=4x | | -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 | | .15x=5.25 | | 3(8+2x)(5+2x)=(14.5+2x)(15+2x) | | x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 | | 5(n+2)+10=20 | | (6x^3-3x^2+4x)-(4x^2+3x+8)= | | 2x/3+20=30 | | 3(x-2)-x=12+5x | | -2/9r=-8 |